Application of value stream mapping for lean implementation: a case study from Indian foundry industry. (2015) - Prasad, Suresh; Sharma, S.K.
Value stream mapping (VSM) is an efficient method that can be utilised in lean environments to recognise opportunities for reduction in production lead time, processing time, and work-in-process (WIP) inventory. The purpose of this paper is to present the results of a successful application of VSM for lean implementation in an Indian foundry industry. Some modifications are proposed in current state map and with these modifications a future state map is prepared. In the present work, both current and future state maps of studied foundry's shop floor are discussed and TAKT time has been calculated to set the pace of production processes. On comparing the current and future state of the shop floor of studied foundry industry, it is found that there were reduction in raw materials inventory, WIP inventory, finished products inventory, production lead time, processing time, and total manpower requirement. Moreover, improvement in output per person has been reported.